Waqf Funds as an Instrument for the Dissemination of Knowledge in Classical Islamic Civilization - Azmi, Ulul; Marpaung, Anton (Al-Qarawiyyin: Jurnal Ilmu Ushuluddin, 2025)
In classical Islamic history, waqf was not only a practice of religious philanthropy but also served as a strategic mechanism supporting the sustainability of education and the development of science. The urgency of this study lies in the lack of historical studies that systematically position waqf as the institutional foundation of science, especially in the context of its relevance to modern educational models. This research aims to analyze the role of waqf in strengthening scientific institutions and examine its management mechanisms that encouraged the sustainability of intellectual activity during the golden age of Islam. Using qualitative methods based on historical-descriptive analysis, this study examines classical works and secondary sources through document analysis of waqf practices in various centers of knowledge during the Islamic Middle Ages. The results show that waqf not only provided funding for mosques but also supported the establishment and management of madrasas, universities, libraries, and study centers such as Bayt al-Ḥikmah in Baghdad and Al-Qarawiyyin in Fez. Furthermore, the scholarship system, teacher allowances, and the provision of research facilities are concrete forms of waqf’s contribution to creating a sustainable scientific ecosystem. These findings reveal that the existence of waqf facilitates the transfer of knowledge across generations and promotes intellectual exchange between the Islamic world and other civilizations. In conclusion, waqf serves as a structural foundation for scientific civilization, not merely a charitable act, and its relevance offers a sustainable model for educational financing that can be applied in contemporary contexts.